Pengembangan Buku Saku IPA pada Materi Macam-Macam Gaya untuk Siswa Kelas IV SD - Nidya Pratiwi; Andriana Sofiarini; Asep Sukenda Egok (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2023)
This study aims to develop and design a Science Pocket Book on Material of Various Styles for Grade IV Students at SD Negeri 8 Lubuklinggau which is valid, practical, and effective to be used in learning. This type of research is Research and Development with the ADDIE development model. Data collection techniques that the authors use are interviews, questionnaires, and tests. Based on the results of the assessment analysis obtained from linguists 0.81, material experts 0.92 who meet the high criteria or are valid while for media experts 0.71 meet the criteria high enough or are valid. Then the results of the practicality analysis of the one to one test students obtained a score of 95.82%, the small group test 93.73% and the teacher obtained 91.66% with a total of 93.73% which met very practical criteria. Furthermore, the results of the effectiveness analysis obtained an average pre-test result of 56.72 and a post-test of 76.20 which were analyzed using the N-Gain formula to obtain a value of 0.450 with a moderate classification. So it can be concluded that the Science Pocket Book on Material of Various Styles for Grade IV Students of SD Negeri 8 Lubuklinggau is valid, practical, and effective in the learning process. Keywords: Pocket Book, Science, Development